2004
DOI: 10.4049/jimmunol.173.9.5583
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Regulates Expression of the MHC Class I-Related Chain A Gene in Activated T Lymphocytes

Abstract: MHC class I-related chain A gene (MICA) is a stress-regulated, HLA-related molecule which exhibits a restricted pattern of expression. MICA protein is up-regulated on different tumor cells, and is recognized by the lectin-like NKG2D molecule expressed by cytotoxic γδ T lymphocytes, CD8+ αβ T lymphocytes, and NK cells. Although MICA is not expressed on resting lymphocytes, we demonstrated that it is induced on activated T cells. Because NF-κB is actively involved in T cell activation, and is constitutively acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 55 publications
6
82
0
5
Order By: Relevance
“…We conclude that NF-B p65 activity is not essential for HDAC-i-mediated MICA/B expression in Jurkat T cells. It has been shown that NF-B activity is important for MICA expression of activated peripheral blood T lymphocytes (44) and our data does not argue against the ability of NF-B activity to further regulate MICA expression.…”
Section: Discussionsupporting
confidence: 51%
“…We conclude that NF-B p65 activity is not essential for HDAC-i-mediated MICA/B expression in Jurkat T cells. It has been shown that NF-B activity is important for MICA expression of activated peripheral blood T lymphocytes (44) and our data does not argue against the ability of NF-B activity to further regulate MICA expression.…”
Section: Discussionsupporting
confidence: 51%
“…Furthermore, a recent study demonstrated the existence of a binding site in the long intron 1 of the MICA gene for NF-kappaB (Molinero, Fuertes et al 2004). It has been shown that physiologic concentrations of male hormones (androgens) cause prolonged NF-kappaB DNA binding activities, which are diminished by vitamins C and E (Ripple, Henry et al 1999)and estrogen inhibits NF-kappa B activity (Ghisletti, Meda et al 2005;Kalaitzidis and Gilmore 2005).…”
Section: Npc Commented Epidemiologic Datamentioning
confidence: 99%
“…Interestingly, expression of MIC genes can be upregulated upon certain stimuli ('cell stress') such as viral infections [33], oxidative stress [34], or heat shock [35]. Furthermore, expression is activated by the NF-kappa B pathway [36] and by DNA damage [37]. MICA and MICB molecules could be shown to be ligands for the strong activating receptor NKG2D (KLRK1) [38,39], which is expressed on NK cells, and T lymphocytes, and macrophages.…”
Section: The Major Histocompatibility Complex (Mhc)mentioning
confidence: 99%